The Future of the Eastern Partnership: "Building a Shared European Home" - Maria Sarakutsa; Maryna Rabinovych (CES Working Papers, 2016)
The year 2014 became a turning point in the history of the EU Eastern Partnership (EaP), marked by the signing of the Association Agreements with three EaP states and a conflict in Ukraine. In view of the above, current research focuses on assessing the feasibility of scenarios of the EaP future, discussed in scholarship, based on the assessment of the EU's foreign policy successes and challenges in Eastern Neighbourhood. EU's internal issues, re-emerging geo-strategic threats and domestic challenges in the EaP states are analyzed. The considered scenarios include the EU's acceptance of the status quo in the region, taking a stronger stance on the integration of Ukraine, Moldova and Georgia, as well as building “a shared European home” by promoting a rapprochement with Russia. The single scenario for the EU's policy in the EaP states is suggested, and the reason why the EU will try to “build a shared European home” is explained.
Keywords: 330; Eastern Partnership; Ukrainian crisis; Association Agreement; geostrategic challenges